Klik, Pesan, Nikmati: Sistem Pemesanan Online Terbaru UMKM Pempek Fenny - Surbakti, Feliks Prasepta Sejahtera; Riofenta , Ignatius Galviandra (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2024)
The development of technology and the COVID-19 pandemic have changed the consumption trends of society. The culinary industry has been affected, but can survive by going online. The Pempek Fenny culinary industry still uses a manual system. This study builds a pempek order information system to improve the information system with various features and measure user satisfaction. The research method uses a mixed method with an action research approach. The population is theculinary industry owner and 6 of its customers purposively. The procedures carried out are problem identification, literature study collection, data collection, system testing, and system evaluation. This finding resulted in efficiency because some activities that were previously done manually can be done automatically by the system with a satisfaction of 3.7. The contribution achieved improves the performance of the culinary industry, the latest features of application development and ordering are more efficient and accurate